2021
DOI: 10.1007/s11356-021-14025-y
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy 3D imaging of diesel particulate matter

Abstract: To date, diesel particulate matter (DPM) has been described as aggregates of spherule particles with a smooth appearing surface. We have used a new colour confocal microscope imaging method to study the 3D shape of diesel particulate matter (DPM); we observed that the particles can have sharp jagged appearing edges and consistent with these findings, 2D light microscopy demonstrated that DPM adheres to human lung epithelial cells. Importantly, the slide preparation and confocal microscopy method applied avoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In order to investigate whether the shapes of particles could be affected by the slide preparation technique, we also prepared slides for confocal microscopy using double-sided adhesive tabs used in scanning electron microscopy in a similar fashion to that we have previously described in a diesel particulate matter imaging study. 11 In essence, the steps were as follows: a piece of filter paper was placed in a plastic Petri dish with a lid. A sample of the underground railway PM was sprinkled on the filter paper using a small spatula and the lid replaced.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to investigate whether the shapes of particles could be affected by the slide preparation technique, we also prepared slides for confocal microscopy using double-sided adhesive tabs used in scanning electron microscopy in a similar fashion to that we have previously described in a diesel particulate matter imaging study. 11 In essence, the steps were as follows: a piece of filter paper was placed in a plastic Petri dish with a lid. A sample of the underground railway PM was sprinkled on the filter paper using a small spatula and the lid replaced.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Previous studies of PM have mostly used 2D light microscopy, scanning electron microscopy (SEM), or transmission electron microscopy (TEM). However, 3D confocal microscopy can provide important additional structural details compared with the 2D techniques as it allows the combination of true color information with 3D visualization. , In a recent confocal imaging study, we observed that diesel particulate matter (DPM), also known as diesel exhaust particulate (DEP), can have a sharp jagged surface appearance …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, microscopy can be used to observe and analyze two-dimensional mitochondrial morphologies and quantities. However, although this method is suitable for analyzing adherent cells with flat morphology, it is not suitable for thicker cells (77)(78)(79)(80)(81)(82)(83). Three-dimensional confocal microscopy can be used to observe mitochondrial morphology by observing specifically labeled mitochondrial proteins at the 3d level (84)(85)(86)(87).…”
Section: Determination Of Mitochondrial Morphology and Structurementioning
confidence: 99%